Teori Transformasi dan Implikasinya pada Pengelolaan Lembaga Pendidikan Islam - Binti Nasukah; Endah Winarti (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2021)
The purpose of articles is to discuss the emergence of the theory of transformation in education, and its implication for Islamic educational management. Departing from the challenges and demands of the need to generating heredity who are creative, innovative, productive and able to contribute to building society, to form a better world civilization, the administration of education requires a new perspective — that is, a transformative perspective. Using this type of literature review research, it was found that the transformative perspective in education was introduced by Mezirow in his theory of transformative learning. Through this theory, the theory of transformative learning develops towards the theory of transformative education in the context of facing globalization and the development of the 21st century. The implication for Islamic educational institutions is the need to focus on quality to become transformative educational institutions.